Upaya Peningkatan Hasil Belajar Permainan Bola Voli Melalui Modifikasi Permainan Bola Panas (Department of Physical Education, Sport, Health and Recreation, 2015)
The research goal is to improve learning outcomes through modification volleyball game ball games hot in the fourth-grade students of SD Negeri Cangkring 01 Talang District of Tegal in physical education subjects. This research is a classroom action research by using two cycles, each cycle consisting of planning, implementation, observation and reflection with the subject of the research that fourth-grade students of SD Negeri Cangkring 01 District Talang Tegal 2014 totaling 27 students consisting of 15 boys and 12 students girl. Results research shows that learning volleyball through a modified hot ball games can improve student learning outcomes of the first cycle to the second cycle. The average value of passing on learning outcomes in the first cycle (77.63), second cycle (79.78). Thus increasing the learning outcomes of the first cycle to the second cycle of (2.15). The number of students who otherwise completed the first cycle of 17 students (62.96%) and the second cycle 25 students (92.59%). The conclusion of this study, that learning the game of volleyball through a modified hot ball game on the fourth-grade students of SDN 01 Cangkring Talang District of Tegal 2014 can improve student learning outcomes.